Annual energy analysis of a building equipped with CaCl2·6H2O as PCM and CaCl2·6H2O/ CsxWO3 as nano PCM – Useless of adding nanoparticles. (1st August 2022) - Alqaed, Saeed; Mustafa, Jawed; Sharifpur, Mohsen
Abstract: Phase Change Materials (PCMs) are just as effective at reducing the energy exchange of a building with its surroundings as thermal insulation. Nanoparticles (NPs), on the other hand, can alter the thermal response of PCMs by altering their thermal properties. In this study, with emphasis on building heat balance, the thermal performance of C a C l 2 · 6 H 2 O as PCM and C a C l 2 · 6 H 2 O / C s x W O 3 as nano PCM were compared. The building heat balance was analyzed annually in numerical analysis. C s x W O 3 nanoparticles were added to C a C l 2 · 6 H 2 O at 0.25, 0.5, 0.75 and 1 wt%. The thermal conductivity and enthalpy of phase change of C a C l 2 · 6 H 2 O both underwent a decreasing trend so that at 1 wt%, the former and latter parameters were decreased by 30.5 and 24.2%, respectively. The performance of the building was first analyzed with C a C l 2 · 6 H 2 O and it was found that it reduces the building heat balance by 8.2%. Heat balance was evaluated for C a C l 2 · 6 H 2 O / C s x W O 3 and it was found that C s x W O 3 have acceptable thermal behavior only at 0.5 wt%. In this mass fraction, the heat balance decreases by 1%, and at 0.25, 0.75, and 1 wt%, it increases by 0.13%, 0.52% and 4.6%, respectively. The most important result was that it is necessary to perform annual calculations to compare the performance of nano-PCM and PCM considering the energy analysis of the building. Highlights: Comparing energy consumption of PCM filled building and nano-PCM filled building. The building heat balance was analyzed annually at nanoparticles mass fraction of 0.25, 0.5, 0.75 and 1. Thermal behavior of nano-PCM at 0.5 wt% was only acceptable owing to energy usage reduction of 1%. At 0.25, 0.75, and 1 wt%, energy usage increases by 0.13%, 0.52% and 4.6%.